KENYAMANAN GAUN DENGAN MENGGUNAKAN POLA MEYNEKE UNTUK WANITA BERBADAN GEMUK DI SURABAYA (Universitas PGRI Adi Buana Surabaya, 2024)
The comfort in wearing clothes can be seen from two criteria, they are size precision and fitting factor precision on the wearer’s body. The precision of fitting factor is a location or spot on clotes that determines the properness of certain pattern system, for the wearing body. Meyneke pattern generally used for cloting fit the body because it has kupnat at the waist that suitable for obese women. The problems of the research that is how the comfort level of woman’s dresses with patters Mayneke obese. The purpose is to know wheather the pattern Meyneke suitable for obese women.This research includes with quantitative approach and its object is the comfort level on points fit, while the subject Meyneke pattern on making a dress with a size XL. The method used is the method of observasion, quistionnare and experiment methods.Based on the results the percentage of questionnaire data, the level of comfort at acomfortable level of usage pattern Meyneke 2,3% in later neckline, 2,9% on alayout position of the shoulder, 3,1% at the position of the body circumference, 3% at the position of concave arm, 3% the layout position kupnat, 3% on the position of waist circumference, 3% on a long standing dress, 3% on the positions of the sides, 3,1% on the back of 2,8% long position for the fall dresses for woman are obese are advised to wear patterns Meyneke because the results are good.